Educational intervention using a mobile app to enhance sports nutrition knowledge and dietary habits in student-athletes: a randomized controlled trial - AlKasasbeh, Walaa Jumah; Amawi, Adam Tawfiq; Al-Nawaiseh, Sabah Jamil; Alshorman, Deefallah; Alshdaifat, Kawthar; Alawamleh, Thekra; Orhan, Bekir Erhan (Frontiers in Education, 2025)
IntroductionThe increasing use of digital tools in education offers innovative ways to improve health behaviors. This study aims to evaluate the effectiveness of a mobile application intervention in enhancing sports nutrition knowledge and improving dietary habits among university student-athletes.MethodsA total of 100 university student-athletes were randomly assigned to either an experimental group (n = 50), which utilized the “MyFitnessPal” mobile application for nutrition education, or a control group (n = 50), which received traditional lecture-based instruction. Both groups completed validated pre- and post-intervention questionnaires over a three-month period to assess changes in sports nutrition knowledge and dietary habits.ResultsThe experimental group showed significantly greater improvements in both sports nutrition knowledge and dietary habits compared to the control group (p < 0.05).DiscussionThese findings suggest that mobile applications like “MyFitnessPal” are more effective than traditional educational methods in enhancing nutritional awareness and promoting healthier dietary behaviors among student-athletes. Mobile application-based interventions can play a key role in improving athletic performance and overall health. Future research should explore the long-term impact and generalizability of such interventions across diverse athletic populations.